THE RELATIONSHIP BETWEEN FATHER'S PARTICIPATION IN COMPLEMENTARY FEEDING AND THE NUTRITIONAL STATUS OF BABIES 6-12 MONTHS - Afrilia Dwi Rosita; Meivita Dewi Purnamasari; Haryatiningsih Purwandari (International Journal of Biomedical Nursing Review, 2026)
Introduction: Proper complementary feeding (MPASI) is an important factor in supporting the growth and development of the baby, especially in determining the nutritional status of the baby. The involvement of fathers in the provision of complementary foods can contribute to the nutritional status of the baby, but there are still many fathers who are less involved in this process. Objective: This study aims to analyze the relationship between fathers' participation in complementary feeding and the nutritional status of infants aged 6–12 months in Gandatapa Village. Methods: This study used a quantitative correlation analysis method with a cross-sectional design. Results: characteristics of fathers with a median age value of 33 years with a majority of high school education, working as laborers and income <UMR Banyumas in 2024. The majority of fathers' participation is classified as sufficient with the normal majority nutritional status. The analysis of the Somers'd test obtained a p-value = 0.292 (p>0.05) which showed that there was no significant relationship between the participation of fathers in the provision of complementary foods and the nutritional status of infants aged 6–12 months in Gandatapa Village. Conclusion: there was no significant relationship between the participation of fathers in the provision of complementary foods and the nutritional status of infants aged 6-12 months in Gandatapa Village.